EVALUASI PROGRAM PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR MELALUI PEMBERIAN KAPAL IKAN BESERTA ALAT TANGKAP DI KABUPATEN TANJUNG JABUNG TIMUR - Asmaida Asmaida (Universitas Batanghari Jambi, 2014)
Government of the District of Tanjabbar East region has conducted a program of the Coastal Community Economic Empowerment (PEMP) implemented in fiscal year 2011 and 2012, namely through the provision of fishing vessels and their gear. This study aims to: 1) analyze the impact of PEMP program through the provision of fishing gear and its fishing boats against the income of fishermen in the coastal area of Tanjung Jabung district. 2) Assess the benefits PEMP program through the provision of fishing vessels and their gear in the Eastern District of Tanjabbar. This study was designed as a descriptive research with case studies, with daaerah coastal locations in East Tanjung Jabung precisely in the district and sub-district Nipah Long Sadu. In this case the fishermen as the primary data source, the data collection techniques of observation, interviews and questionnaires, the need for data that refers to the topic and title research, and related agencies, literature-literature as a source of secondary data. Respondents were randomly assigned, namely the fishermen and their fishing boats receiver tangka tool of implementation PEMP program, as many as 127 people or ± 26% of the total population of 422 people. The results showed that the implementation of the Coastal Community Economic Empowerment Program (PEMP) through the provision of fishing vessels and their fishing gear, in the utilization of water potential and economic development of coastal communities (fishermen) are able to give good results in line with expectations and objectives of the program. The average income of fishermen to fishing before PEMP program is Rp 5.881739, - / month and after the program PEMP of 9,779,905, - / month. This revenue rose about Rp 2,721,205, - / month or by 66.28% from the previous. Changes in the income of fishermen, of statistical tests performed with a confidence level of 95%, there are significant PEMP program through the provision of fishing vessels and their fishing gear to catch fishermen's income changes before and after the program in the District of Tanjabbar PEMP East. Factors that affect the fishermen's income is the number of family members, the amount of venture capital, and natural conditions are not favorable. Some things must be considered in the implementation of programs PEMP for the purpose of implementation of the program can be a maximum terujud accordance with the results obtained in the field, which are: 1) Keep monitoring and evaluation of program implementation as a whole, and the emphasis on outputs and impact of the program. 2) It should be formulated priorities that programs can be implemented as a refinement of PEMP programs that have been adapted to the problems faced by the community. 3) Keep the adjustment program given to the conditions in the field, so that appropriate and targeted.Keyword : evaluation, economic empowerment, fishing boats